Does defibrotide induce a delay to polymorphonuclear neutrophil engraftment after hematopoietic stem cell transplantation? Observation in a pediatric population. - Maximova, Natalia; Pizzol, Antonio; Giurici, Nagua; Granzotto, Marilena (Adv Ther, 2015)
INTRODUCTION: In recent years, defibrotide (DFT) has emerged as a promising therapy for veno-occlusive disease (VOD). The aim of this study was to investigate whether DFT prophylaxis affects neutrophil engraftment in patients undergoing hematopoietic stem cell transplantation (HSCT). METHODS: A cohort of 44 consecutive pediatric patients who underwent HSCT was retrospectively analyzed to see the role of DFT on engraftment. Patients were assigned into two groups based on the use or non-use of prophylaxis with DFT. RESULTS: The mean time to engraftment was statistically different between the two groups for both polymorphonuclear neutrophils (PMN) and white blood cells. CONCLUSION: Our study supports the hypothesis that prophylaxis with DFT for VOD leads to a delay to the engraftment of PMN in pediatric patients that underwent HSCT.